Pentingnya Pelatihan Sumber Daya Manusia Dalam Upaya Meningkatkan Kreativitas Dan Inovasi Produk Kopi Pada Desa Mekarbuana Kabupaten Karawang - Wike Pertiwi; Ery Rosmawati (SOCIRCLE : Journal Of Social Community Services, 2023)
This community service activity aims to improve human resources in creative and innovative thinking in the development of coffee products. Partners in this service work together with Buana Mekar Bumdes. The method of service is in the form of training and assistance in improving human resources. The final expected goal is for partners to collaborate in achieving increased sales of sanggabuana coffee.